Heavy metals in the organic soil layer of beech forests in Serbia - Kadović Ratko; Košanin Olivera; Belanović Snežana; Knežević Milan (Glasnik Šumarskog Fakulteta: Univerzitet u Beogradu, 2005)
During the last decades, forest ecosystems have been strongly exposed to the effect of different harmful pollutants, especially from the atmosphere. Harmful substances from the air, in addition to the direct effect on forest trees, also deposit in the soil, and have an adverse effect on soil chemistry and pedogenetic processes. The results of previous studies in Serbia (Kadović, Knežević, 2002, 2004) show some specificities regarding the accumulation and migration of heavy metals in the soil. The highest concentrations were found in the layers of forest litter and in the surface organo-mineral horizons. This paper presents the results of the study of heavy metal contents (Zn, Mn, Cu, Fe, Cd, Pb, Ni and Cr) in the organic horizon (forest litter) of beech forests in Serbia. The study of the heavy metal content in the organic horizon (forest litter) is very significant primarily in the aim of monitoring the trend of their migration through the soil profile and the effect on the soil properties and genesis. The soil quality in beech forests in Serbia was assessed within the Project ICP Forest, Level I, by the methodology UN/ECE-EC, 2000.